Development of National University Web-Based Digital Library Information System: Development of National University Web-Based Digital Library Information System - Rahmat Aji Santoso; Agung Triayudi; Winarsih Winarsih (Jurnal Mantik, 2020)
The library is one of the sources to acquire: science. In the library: There is a collection of collections in the field of good science in the form of: books, journals, Proceedings, & Thesis as well as other types of reading. With the development of information technology and the implementation of information systems in various aspects of life: there are also many libraries that utilize information technology as a tool in place to facilitate operational activities in the library. In the field of education, schools and colleges, libraries are: the one condition for college to stand. One of the colleges that have also utilized the information Technology Library is: National University. UNAS's library has also used information systems to manage books and other reading resources in the library. In addition, the process of borrowing and refunding and registration of members has been made also computerized with the presence of the library information system. Library members can also: Use the catalogue of books found in the columns in the library to search for the desired library title. Therefore, authors developed a "Digital Library" website based on: "Development of Digital Library Information System WEB based National University" so this makes it easier for members to be able to also access the library title from elsewhere, without having to come into the library.